Learning Obstacles Faced by Elementary Students in Solving Mathematical Problems on Rectangles and Squares - Sidik, Geri Syahril; Nur Anisa, Siska; Fatimah Zahrah, Riza; Fitri Apriani, Ika; Jenal Mutaqin, Ejen; Komalasari, Elis (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to identify student learning obstacles in solving mathematical problems on rectangular and square materials in grade IV elementary school. Method: The study employed a Didactical Design Research (DDR) method with a descriptive qualitative approach. The research involved 20 students, with six selected for in-depth interviews. Data were collected through diagnostic tests, semi-structured interviews, observation, and documentation. Data analysis followed the three stages of DDR: prospective analysis to identify potential learning obstacles before instruction, metapedadidactic analysis to examine learning interactions during instruction, and retrospective analysis to evaluate overall learning outcomes. Results: The results revealed five major difficulties encountered by students: understanding problem contexts, representing problems in mathematical form, performing arithmetic operations, communicating answers, and generalizing solutions. These difficulties indicate learning barriers categorized as ontogenic (related to students’ cognitive readiness and development), epistemological (related to students’ understanding of mathematical concepts), and didactic (related to instructional approaches and strategies). Novelty: This study highlights the necessity of contextual, interactive, and visually concrete learning supports to foster meaningful understanding of geometry concepts. It also underscores the significance of DDR-based instructional design in addressing student learning needs and promoting innovative mathematics teaching strategies in primary education.